Mixing de IITJEE Problèmes...

Level pending

Consider the lines

L 1 L_{1} : x + 1 3 \frac{x+1}{3} = y + 2 1 \frac{y+2}{1} = z + 1 2 \frac{z+1}{2}

&

L 2 L_{2} : x 2 1 \frac{x-2}{1} = y + 2 2 \frac{y+2}{2} = z 3 3 \frac{z-3}{3}

(Following Equations Represents Equation of Line In 3 Dimensional Cartesian Coordinate System)

If the unit vector perpendicular to both L 1 L_{1} and L 2 L_{2} can be written as

a i ^ b j ^ + c k ^ d e \frac{a\hat{i}-b\hat{j}+c\hat{k}}{d\sqrt{e}} ; where i ^ , j ^ , k ^ \hat{i}, \hat{j}, \hat{k} are unit vectors along x-axis, y-axis, z-axis respectively and a,b,c,d,e \in R

*Now if f ( x ) f(x) a function which is differentiable and *

0 t 2 x f ( x ) d x \int_0^{t^{2}}xf(x)dx = 2 5 t 5 \frac{2}{5}t^{5}

then f ( e a c d f(\frac{e-a}{cd} ) = α β \frac{\alpha}{\beta}

where β > α \beta > \alpha

Then value of 1 + ω α + β + ω 2 b 1 + \omega^{\alpha + \beta} + \omega^{2b} =

(Where ω \omega is imaginary cube root of unity)

0 1 - i i i i

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Harshil Patel
Feb 11, 2014

From L 1 L_{1} & L 2 L_{2} we get direction ratio's of L 1 L_{1} = (3,1,2) and L 2 L_{2} = (1,2,3)

So, Perpendicular vector to L 1 L_{1} and L 2 L_{2} is ( 3 , 1 , 2 ) × ( 1 , 2 , 3 ) (3,1,2) \times (1,2,3) [Cross Product of 2 Vectors]

We get vector perpendicular to both lines as A ˉ \bar{A} = 1 i ^ 7 j ^ + 5 k ^ -1\hat{i}-7\hat{j}+5\hat{k}

We know unit vector of any vector is = A ˉ A ˉ \frac{\bar{A}}{|\bar{A}|} [Where A ˉ |\bar{A}| is magnitude of A ˉ \bar{A} ]

So, unit vector A ^ \hat{A} = 1 i ^ 7 j ^ + 5 k ^ 5 3 \frac{-1\hat{i}-7\hat{j}+5\hat{k}}{5\sqrt{3}}

Implies, a=-1, b=7, c=5, d=5, e=3

Now, we have 0 t 2 x f ( x ) d x = 2 5 t 5 \int_0^{t^{2}} xf(x)dx = \frac{2}{5}t^{5} ,

Differentiating both side by using Newton-Leibnitz's Formula we get t 2 ( f ( t 2 ) [ d d x t 2 ] 0 = 2 t 4 t^{2}(f(t^{2})[\frac{d}{dx}t^{2}] - 0 = 2t^{4}

Solving Further we are left with f ( t 2 ) = t f(t^{2})=t

e a c d = 3 ( 1 ) 25 = 4 25 = ( 2 5 ) 2 \frac{e-a}{cd} = \frac{3-(-1)}{25} = \frac{4}{25} = (\frac{2}{5})^2

\implies f ( [ 2 5 ] 2 ) = 2 5 = α β f([\frac{2}{5}]^2) = \frac{2}{5} = \frac{\alpha}{\beta}

\implies α = 2 , β = 5 \alpha = 2 , \beta = 5

α + β \alpha + \beta = 7

and 2 b 2b = 14

*So, according to given equation 1 + ω α + β + ω 2 b 1+\omega^{\alpha+\beta}+\omega^{2b} = *

* 1 + ω 7 + ω 14 1+\omega^{7}+\omega^{14} and using property of ω \omega *

ω 3 n + 1 = ω , ω 3 n + 2 = ω 2 \omega^{3n+1} = \omega , \omega^{3n+2} = \omega^{2}

* = 1 + ω + ω 2 1+\omega + \omega^{2} *

now , ω = 1 + 3 i 2 , ω 2 = 1 3 i 2 \omega = \frac{-1+\sqrt{3}i}{2} , \omega^{2} = \frac{-1-\sqrt{3}i}{2}

\implies ω + ω 2 = 1 \omega + \omega^{2} = -1

so , 1 + ω + ω 2 1+\omega + \omega^{2} = 1-1 = 0 \boxed{0}

Reference :- Line In 3-D Root of Unity Leibniz Integral Rule

Your problem seems to have two answers. As f ( t 2 ) = t f(t^2)=t , so from what we get after applying Newton-Leibnitz differentiation, i.e. f ( 4 25 ) = ± 2 5 \displaystyle\,f(\frac{4}{25})=\pm\frac{2}{5} which in turn yields two possible answers as 2 + ω 2 2+\omega^2 & 0 0 .

Nishant Sharma - 7 years, 3 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...